2020
DOI: 10.1080/14756366.2019.1706502
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and antiprotozoal evaluation of new 2,4-bis[(substituted-aminomethyl)phenyl]quinoline, 1,3-bis[(substituted-aminomethyl)phenyl]isoquinoline and 2,4-bis[(substituted-aminomethyl)phenyl]quinazoline derivatives

Abstract: Courtioux (2020) Design, synthesis, and antiprotozoal evaluation of new 2,4-bis[(substitutedaminomethyl)phenyl]quinoline, 1,3-bis[(substituted-aminomethyl)phenyl]isoquinoline and 2,4bis[(substituted-aminomethyl)phenyl]quinazoline derivatives,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…[34,35] We found that sugar conjugated naphthalene diimides previously shown to be G4 ligands [36] also bind G4s found exclusively in T. brucei and present very notable antiparasitic activity. [33,37,38] Eventually, other quadruplex ligands such as quarfloxin, CX-5461 [39] and compounds based on stiff stilbene, [40] naphthalene diimide, [41] perylene diimide, [42] phenantroline, [43,44] quinoxaline [45] and quinoline scaffolds [46] have been reported with antitrypanosomal and antiplasmodial activity. [47] In this work, we studied the presence of PQS in the genome of Trypanosoma cruzi and carried out biophysical studies confirming that some of these frequent PQS actually form stable quadruplex structures.…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] We found that sugar conjugated naphthalene diimides previously shown to be G4 ligands [36] also bind G4s found exclusively in T. brucei and present very notable antiparasitic activity. [33,37,38] Eventually, other quadruplex ligands such as quarfloxin, CX-5461 [39] and compounds based on stiff stilbene, [40] naphthalene diimide, [41] perylene diimide, [42] phenantroline, [43,44] quinoxaline [45] and quinoline scaffolds [46] have been reported with antitrypanosomal and antiplasmodial activity. [47] In this work, we studied the presence of PQS in the genome of Trypanosoma cruzi and carried out biophysical studies confirming that some of these frequent PQS actually form stable quadruplex structures.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a number of recent papers describe the discovery and development of G4‐ligands with anti‐parasitic activity. [ 16a , 18 ] Among the different molecular scaffolds, 2,9‐bis[(substituted‐aminomethyl)phenyl]‐1,10‐phenanthroline,[ 18c , 18g ] napthalene diimide,[ 16c , 18d , 18f , 18h , 18i ] and quinazoline [18e] derivatives have been reported to show promising in vitro anti‐trypanosomal activity and selectivity (Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“… Representative examples of G4‐ligands with reported anti‐trypanosomal activity and selectivity: 2,9‐bis[(substituted‐aminomethyl)phenyl]‐1,10‐phenanthroline, [18c] carbohydrate conjugated naphthalene diimide, [16a] and 2,4‐bis[(substituted‐aminomethyl)phenyl]quinazoline. [18e] …”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic rings with nitrogen and sulfur are therapeutically and pharmacologically reported active and are of particular interest [ 18 ]. Quinazoline derivatives are heterocyclic molecules with nitrogen fixed in the ring that exhibit antiviral, antidiabetic, antimalarial, antioxidant, and anti-inflammation characteristics, to mention a few [ 3 , 6 , 10 , 14 , 20 ]. In recent years, several medications, such as 2-anilino 4-amino substituted quinazolines, have shown antimalarial efficacy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%